Assessment of Myocardial Viability in Patients with Chronic Total Occlusion Using Cardiac MRI Scan - Shah, Syed Akmal; Javaid, Syed Yasser; Bhatti, Qamar uz Zaman; Siddique, M Bilal; Ghous, M Waleed; Farhan, Shaheer; Azad, Naseem (Indus Journal of Bioscience Research, 2025)
Objective: To assess myocardial viability in patients with chronic total occlusion using cardiac MRI scan. Study Design: Prospective cross-sectional study. Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Disease Rawalpindi Pakistan, 1st Dec 2024 to 1st March 2025. Methodology: Seventy-two patients with chronic total occlusion confirmed on coronary angiography were enrolled and further assessed using cardiac MRI. Initial imaging was performed for heart positioning, followed by acquiring standard cardiac planes for anatomical assessment. Gadolinium contrast was administered to evaluate myocardial viability. After a delay of 10–15 minutes, late gadolinium enhancement (LGE) imaging was conducted to detect scar and fibrosis. The LGE images were analyzed to determine the location, extent, and transmurality of the scar. Myocardial segments corresponding to the affected vascular territories were systematically assessed to differentiate between viable (<50% LGE) and non-viable (>50% LGE) myocardium. Results: The study included 72 participants, with a predominant representation of males, 63(87.5%), The mean age of participants was 65.97±8.39 years. Cx had the highest viability 64(88.9%), followed by the RCA 52(72.2%) and LAD 46(63.9%). Conversely, non-viability was least prevalent in LCx 8(11.1%) and highly prevalent in LAD 26(36.1%), indicating that the LAD artery exhibited the most compromised viability among the three major coronary arteries. Conclusion: Cardiac MRI is a valuable tool for assessing myocardial viability in patients with chronic total occlusion, aiding in clinical decision-making for revascularization. The study highlights that the LAD artery exhibits the most compromised viability.